1995
DOI: 10.1507/endocrj.42.235
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Prolactin Secretion in Normal and Estrogen-Treated Pituitaries of Rats at the Single Cell Level: Analysis by Reverse Hemolytic Plaque Assay.

Abstract: Abstract.We studied PRL release from individual pituitary cells in normal and estrogen (E2)-treated female Fischer 344 rats by means of a reverse hemolytic plaque assay. In this assay, the area of the hemolytic plaque around a pituitary cell is proportional to the amount of hormone secreted from the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…These results agree with a previous report showing no differences in basal PRL secretion between E 2 -induced adenoma and normal pituitaries, estimated by RIA (Yoshikawa et al 1995). In addition, these authors found a smaller mean plaque area for E 2 -treated cells from F344 rats using the reverse hemolytic plaque assay (RHPA), suggesting a lower PRL release rate in E 2 -induced tumor cells (Yoshikawa et al 1995). This observation could be in line with the low levels of exocytotic protein components detected in pituitary glands of E 2 -treated rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with a previous report showing no differences in basal PRL secretion between E 2 -induced adenoma and normal pituitaries, estimated by RIA (Yoshikawa et al 1995). In addition, these authors found a smaller mean plaque area for E 2 -treated cells from F344 rats using the reverse hemolytic plaque assay (RHPA), suggesting a lower PRL release rate in E 2 -induced tumor cells (Yoshikawa et al 1995). This observation could be in line with the low levels of exocytotic protein components detected in pituitary glands of E 2 -treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that neither the basal nor 8-Br-cAMP-induced PRL release in cultured cells from E 2 -treated animals differs from that in control donors. These results agree with a previous report showing no differences in basal PRL secretion between E 2 -induced adenoma and normal pituitaries, estimated by RIA (Yoshikawa et al 1995). In addition, these authors found a smaller mean plaque area for E 2 -treated cells from F344 rats using the reverse hemolytic plaque assay (RHPA), suggesting a lower PRL release rate in E 2 -induced tumor cells (Yoshikawa et al 1995).…”
Section: Discussionsupporting
confidence: 91%